Achievements of Study Concerning Worm Face Gear Made in Romania - Vasile Boloş (Scientific Bulletin of the ''Petru Maior" University of Tîrgu Mureș, 2010)
Worm face gears are a relatively new category of gear failure in 50 years in the USA. They are composed of a conical or cylindrical worm to engage the front wheel of a conical or flat. Geometric configuration to ensure a great contact ratio and lubrication between the flanks favorable conditions which allow their implementation of hardened steel, gray iron, bronze. Also they will produce big rapport of transmission in a single stage. Originally conceived by Illinois Tool Works Company Chicago they were taken and developed at the Institute of Mechanical Izhevsk (Russia). Experimental and theoretical developments were made in Britain, Germany, Hungary, Poland, Bulgaria and Romania. In the present paper is highlighted the concerns and the achievements of researchers from Romania in the period 1980-2009.